PENGARUH KARAKTERISTIK DAN AKSES INFORMASI TERHADAP PEMBERIAN PERSETUJUAN TINDAKAN MEDIS (INFORMED CONSENT) DI PUSKESMAS SAMBAS KOTA SIBOLGA TAHUN 2020 - Sonataelina Togatorop; Arifah Devi Fitriani; Razia Begum Suroyo (JURNAL KESMAS DAN GIZI (JKG), 2021)
Approval of medical action is the consent obtained by the doctor after the patient is given information and explanation prior to the procedure.. The purpose of this study was to determine the influence of characteristics and access to informed consent at the Sambas Health Center, Sibolga City. This type of research is a cross sectional design approach. This research was carried out by the Sambas Health Center, Sibolga City. The study population was outpatients and was given medical approval at the Sambas Health Center, Sibolga City. Samples were obtained using a total sampling of 32 people. Data were analyzed by univariate, bivariate (Chi Square), Multivariate (logistic regression).Based on the results of the study, it was found that from 33 respondents, the majority aged 21-40 years 51.5%, the majority were female 51.5%, the majority had high school education 57.6%, the majority did not work 39.4%, the majority were Muslim 78.8 %, the majority of the dominant ethnic group is Batak 81.8%. Bivariate analysis found that there was an effect of education (p= 0.054), occupation (p= 0.050) and access to information (p= 0.016) on informed consent. Multivariate analysis of the variables that have the greatest influence on Informed Consent is access to information with a value of 0.016 and Exp (B) 10.500. Based on these results, it was concluded that there was an effect of education, employment and access to information on Informed Consent. The research suggestion is that the delivery of information must be adjusted to the characteristics of the approver, especially those related to the level of education, so that if things happen that are not desirable after the medical action, it is hoped that the patient or family will be ready to accept them because before the medical action was carried out, the doctor had already received an explanation.